Helicobacter pylori infection and micronutrient deficiencies - Yakoob, Javed (World J Gastroenterol, 2003)
It is known that deficiencies of micronutrients due to infections increase morbidity and mortality. This phenomenon depicts itself conspicuously in developing countries. Deficiencies of iron, vitamins A, E, C, B12, etc are widely prevalent among populations living in the third world countries. Helicobacter pylori (H pylori) infection has a high prevalence throughout the world. Deficiencies of several micronutrients due to H pylori infection may be concomitantly present and vary from subtle sub-clinical states to severe clinical disorders. These essential trace elements/micronutrients are involved in host defense mechanisms, maintaining epithelial cell integrity, glycoprotein synthesis, transport mechanisms, myocardial contractility, brain development, cholesterol and glucose metabolism. In this paper H pylori infection in associaed with various micronutrients deficiencies is briefly reviewed.